Adaptive user behavior's evaluation method based on network status - You LU; Jun-zhou LUO; Wei LI; Feng YU; Nu XIA (Tongxin xuebao)
Abstract:With the development of network, user's complex and dynamic behaviors often lead to unexpected fluctuations of network status,and these fluctuations take great challenge to the stability of network. It is difficult to evaluate user be-havior's affection on network status fluctuations for traditional methods because of their subjectivity and static drawbacks. An evaluation method was proposed, which analyses the correlation between the user's behavior and network status fluc-tuations based on actual data of behavior and network status,by means of rough set attribute reduction and attribute im-portance. This method can construct and dynamically adjust the evaluation indexes and their weight adaptive the actual data. The evaluation results show this method can help to detect and manage users who affect the stability of net-work, and provide effective support to control users and their beha ior.